Immunocytochemistry and heterogeneity of rat brain vimentin - Mares, V; Viklický, V; Gerstein, L M; Dráber, P; Ciesielski-Treska, J (Histochemistry, 1988)
In unfixed cryostat sections of the brains of early postnatal and adult rats, we screened for cells containing vimentin-positive intermediate filaments (VI+-IFs) by applying a panel of four monoclonal antibodies (Mabs VI-01, VI-02, VI-05 and VI-5B3) using indirect immunofluorescence. All of the Mabs stained VI+-IFs in the stromal part of the choroid plexus, in endothelial cells of blood vessels and in meninges in both adult and immature brains, although with varying strength (VI-5B3 and VI-01 stained more strongly than VI-05 and VI-02). In the brain parenchyma of adults, intense staining was mainly localized in ventricular ependymal cells (VI-5B3/VI-01 greater than VI-02/VI-05) and fibrous astrocyte-like cells (FAs). In the immature brain, the ependymal cells were activated in appearance, with evidence of cell enlargement, greater spreading of VI+-IFs within the cytoplasm and more pronounced VI+ cytoplasmic protrusions into the brain parenchyma. VI+-FAs were found near the ependymal and meningeal borders as well as in the white matter tracts of adult brain (VI-5B3/VI-01 greater than VI-05 greater than VI-02). In immature animals, VI+-FAs were less frequently encountered in the forebrain regions, except in and near the subepenydmal layer (in the adjacent parenchyma) as well as in submeningeal layers. Weaker staining was usually elicited by Mabs VI-02 and VI-05. In the cerebellum, Bergmann cell fibers were stained in both age groups. In adults, the most intense fluorescence usually occurred in segments close to the pia (VI-5B3/VI-01 greater than VI-05 greater than VI-02).(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Rats; imunohistochemie; Astrocytes; monoklonální protilátky; mužské pohlaví; Antibodies, Monoclonal; mozek; krysa rodu Rattus; astrocyty; Immunohistochemistry; Brain; ženské pohlaví; zvířata; vimentin; Fluorescent Antibody Technique; Female; Vimentin; fluorescenční protilátková technika; Male; Animals